An Integrated Firewall System Model In A Multiclient-Server Environment - Al-Kazwini, Hussein A. Taqi (2005)

(untitled)
As the Internet grows, and the use of computers is getting more common, the need to secure networks and protect them from the Internet, while still being able to access it, is increasing. The easiest way to achieve a lot of this protection is through firewalls. Firewall technology is the most widely deployed security technology on the Internet. Firewalls have been around for several years. They are a fact of life on the Internet and it is not likely they will disappear in the future. Ongoing development and research in the field of firewall technology have shown a continually addition of features and services to conventional firewall systems.This thesis introduces a new concept for applying the security policy rules by both firewall administrators and users. The proposed firewall system solves some known problems which arise with the use of conventional firewalls residing at the networks perimeter. The developed firewall system integrates the main network firewall and the second-line firewalls into one system by the use of client/server technology to facilitate firewall configuration in a way that affords more convenience to users providing the new integrated firewall using multiclient-server scheme. It centralizes security functions in a single point, simplifying configuration and administration. The new system makes it easier to configure and administrate a firewall in a way in which it is not a source of annoyance to users which offering them higher level of flexibility by giving them the chance to participate in the process of configuration of the firewall using the client side of the system and without affecting the network security policy. It also makes the progress of configuration and administration of the firewall system smoother by reducing the administrator efforts to maintain the system. Good results have been achieved by using the program package. Results show that this system helps keeping the network traffic as low as possible, increasing the efficiency of the network and reducing the threats of malicious data passing in the network. It reduces the efforts and cost of overall system administration and maintenance as well. In addition, it affords users a system which is acceptable and preferable more than conventional firewall systems.